2018
DOI: 10.1007/s00792-018-1026-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on diazotrophic activity and microbial composition of phototrophic communities from Bitter-1 soda lake (Kulunda Steppe, Russia)

Abstract: Bitter-1 is a shallow hypersaline soda lake in Kulunda Steppe (Altai region, Russia). During a study period between 2005 and 2016, the salinity in the littoral area of the lake fluctuated within the range from 85 to 400 g/L (in July of each year). Light-dependent nitrogen fixation occurred in this lake up to the salt-saturating conditions. The rates increased with a decrease in salinity, both under environmental conditions and in laboratory simulations. The salinities below 100 g/L were favorable for light-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The latter family members might be reversed acetogens, able to oxidize acetate in syntrophy with methanogens or SRB, or they might be hydrogenotrophic acetogens [35, 41]. The most abundant 16S rRNA gene transcripts were assigned to Nodosilinea (relative abundance ~ 17%; a genus of haloalkaliphilic, filamentous benthic Cyanobacteria [42, 43]) in the 0–2-cm layer of sediments and to Nitriliruptoraceae (~ 17%; a family of putative nitrile-hydrolyzing Actinobacteria [44]) in the 2–4-cm layer (Additional file 5: Figure S3), groups from which we recovered 1 and 38 different MAGs, respectively (Additional file 4: Dataset 1).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The latter family members might be reversed acetogens, able to oxidize acetate in syntrophy with methanogens or SRB, or they might be hydrogenotrophic acetogens [35, 41]. The most abundant 16S rRNA gene transcripts were assigned to Nodosilinea (relative abundance ~ 17%; a genus of haloalkaliphilic, filamentous benthic Cyanobacteria [42, 43]) in the 0–2-cm layer of sediments and to Nitriliruptoraceae (~ 17%; a family of putative nitrile-hydrolyzing Actinobacteria [44]) in the 2–4-cm layer (Additional file 5: Figure S3), groups from which we recovered 1 and 38 different MAGs, respectively (Additional file 4: Dataset 1).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the ecosystem of soda lake Tanatar VI includes water body, its littoral area and surrounding soils. Tanatar VI represents a highly dynamic ecosystem with long-standing fluctuations of salinity, which cause succession of phototrophic communities that was not observed in the other studied soda lakes of this region (Namsaraev et al, 2018;Samylina et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Samples of phototrophic biomass were collected from the brine, littoral area, and surface of the moist soil surrounding the lake. Salinity, pH, soluble carbonate alkalinity and potential nitrogen fixation (NF) measurements, as well as identification of algae and cyanobacteria, were performed similarly to previous studies (Samylina et al, 2014;2019;Namsaraev et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent microbiological studies of Kulunda steppe soda lakes have led to the isolation of several new taxa of alkaliphilic prokaryotes [18–27] and to the characterization of various microbial processes taking place in these habitats [28–39]. In particular, it was shown that the dead biomass of the primary producers could serve as a source of proteins and peptides for numerous proteolytic bacteria, including members of the phylum Firmicutes Proteinivorax tanatarense [40, 41] and Proteinivorax hydrogeniformans [42] or Candidatus ‘Cyclonatronum proteinivorum’ of the phylum Balneolaeota [43].…”
Section: Full-textmentioning
confidence: 99%